Improving Students Ability to Evaluate and Conclude Through A Scientific Approach - Syukri, Muhammad; Basri, Mahdalena; Halim, A; Maghfirah, Siti (Current STEAM and Education Research, 2025)
This study aims to improve students' assessment and inference skills through the application of the scientific approach. The research was conducted with a pre-experimental design using the single group pretest-posttest method. The study population involved 85 students of class XI of SMAN 1 Blangpegayon, and 22 students of class XI science 2 were selected as samples using purposive sampling. Essay tests on sound waves were used to assess students' critical thinking skills through pretest and posttest. Data were analyzed using N-Gain test and paired sample t test. The results showed that students' evaluation ability had an N-Gain value of 0.97, while the ability to conclude reached 0.99, both of which were classified as high. Hypothesis testing showed a significant difference between pretest and posttest scores with a value of 0.001 <0.05, based on the paired sample t test. Thus, it can be said that employing a scientific approach to the learning process can enchance the capacity to evaluate and conclude students